Review of the Success of Collecting Donations for Palestine through Kitabisa.com - Ichsan, Nurul; Gymnastiar, Rakha Mulia; Zehra, Maria (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
Donating infaq and shodaqah is recommended in Islam. Kitabisa.com provides fundraising services to donate to the campaign for Palestine. This study analyzes the factors influencing the success of collecting infaq and shodaqah donations for Palestine through kitabisa.com. The method used is quantitative, with data collection through questionnaires distributed to 105 people who donated to Palestine at kitabisa.com. Data analysis was carried out using data quality tests and partial least squares (PLS) with the help of SmartPLS3. The dependent variable can be explained by the independent variable by 59.6%, which is classified as moderate. The results showed that religiosity significantly affects donation decisions with a P-value of 0.026. Social influence has no significant effect with a P-Value of 0.696, while project quality significantly affects donation decisions with a P-Value of 0.000. These findings suggest that donors are more likely to donate when they feel influenced to have a strong religious awareness and confidence in the project's quality.